2005
DOI: 10.1080/13803390490490515720
|View full text |Cite
|
Sign up to set email alerts
|

Face Emotion Perception and Executive Functioning Deficits in Depression

Abstract: Frontal, limbic and temporal regions of the brain important in emotion perception and executive functioning also have been implicated in the etiology and maintenance of depression; yet, the relationships among these topics remain poorly understood. The present study evaluated emotion perception and executive functioning among 21 depressed women and 20 nondepressed women controls. Depressed women performed significantly worse than controls in emotion perception accuracy and in inhibitory control, an aspect of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
157
6
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 173 publications
(178 citation statements)
references
References 63 publications
12
157
6
3
Order By: Relevance
“…This view would be consistent with a recent meta-analysis by Fusar-Poli et al (2006), in which acute trytophan depletion was found to modulate cortical activity in areas that are Langenecker et al (2005). The authors reported executive impairments and deficits in the perception of emotional faces that were unrelated in depressed patients.…”
Section: Major Depression and Prosody Comprehension 557supporting
confidence: 88%
See 2 more Smart Citations
“…This view would be consistent with a recent meta-analysis by Fusar-Poli et al (2006), in which acute trytophan depletion was found to modulate cortical activity in areas that are Langenecker et al (2005). The authors reported executive impairments and deficits in the perception of emotional faces that were unrelated in depressed patients.…”
Section: Major Depression and Prosody Comprehension 557supporting
confidence: 88%
“…Emotional prosody is more demanding than facial affect processing, as accuracy scores for the perception of emotional faces are usually higher than prosody accuracy scores (Johnstone & Scherer, 2000). In addition, depressed women in the study by Langenecker et al (2005) were not inpatients and depression levels were relatively low.…”
Section: Major Depression and Prosody Comprehension 557mentioning
confidence: 87%
See 1 more Smart Citation
“…It has been found that patients with acute depressive episodes are less accurate in classifying emotional content and less effective in inhibiting attention to it than healthy controls. 28,29 These deficits are accompanied by altered functioning of the frontal and cingulate cortex as well as subcortical regions, such as the amygdala and basal ganglia. [30][31][32] Family history of MDD may enhance these tendencies.…”
Section: Introductionmentioning
confidence: 99%
“…Certains auteurs montrent que la reconnaissance de l'ensemble des émotions est modifiée par la dépression et entraîne des cognitions erronées [26,38]. Cependant, le lien entre émotion et cognition reste imprécis [3,30].…”
Section: Introductionunclassified